The Role of Industrial Internships in Developing Work Self-Efficacy for Automotive Engineering Students - Tafakur; Hadi, Samsul; Zainal Arifin; Sudji Munadi (Journal of Technical Education and Training, 2024)
Ideally, vocational education graduates have the readiness and desire to work after graduation through various experiences at school. Industrial internships in vocational education are expected to support graduates’ readiness to know the world of work according to their field of expertise. An anomaly, where so far it is suspected that there are still many vocational education graduates who are unemployed or work because they do not have the desire to work. This study aims to understand the role of the student experience in participating in an industrial internship program on automotive students’ work self-efficacy at Yogyakarta State University (YSU). This is survey research with a student population of 102 people. A questionnaire was given to sample of industrial internship participants who were taken at simple random sampling from 91 people. The data were analysed using quantitative descriptive method and Partial Least Square Structural Equation Models using Smart PLS 3 software. The results showed that the developed instrument was proven to be valid for use and had a good estimate of reliability. Most students get internship experience in the good and very good categories. Some students have work self-efficacy in the high and very high categories after industrial internships. The experience of participating in industrial internships is proven to have a positive and significant contribution to student work self-efficacy. It is important for vocational education institutions, especially in the automotive sector, to support industrial internship programs that provide an optimal student experience.